Comparative transcriptomics to reveal muscle-specific molecular differences in the early postmortem of Chinese Jinjiang yellow cattle. (15th December 2019) - Yu, Qianqian; Tian, Xiaojing; Sun, Chengfeng; Shao, Lele; Li, Xingmin; Dai, Ruitong
Highlights: Transcriptome of LL and PM muscles during early postmortem were analyzed. LL and PM showed significant differences in transcriptome profiles. A total of 65 DEGs were found and most of them occurred at 12 h postmortem. Transcriptomics results indicated oxidative phosphorylation was a critical pathway. Abstract: Differences in the expression of functional genes between beef Longissimus Lumborum (LL) and Psoas Major (PM) are not well understood. The aim of present study is to reveal transcriptome changes of beef LL and PM during early postmortem by high-throughput Illumina Hiseq4000 Sequencing. Hierarchical clustering analysis indicated significant differences in transcriptome profiles between LL and PM as well as 1 h and 12 h postmortem. A total of 65 genes differentially expressed between LL and PM (fold change ≥3, and p  < 0.05; 34 were up-regulated in LL and 31 in PM), and the majority of them (53 genes) occurred at 12 h postmortem. These differentially expressed genes mainly involved in energy production and conversion, nucleotide metabolic, posttranslational modification, and transcription. KEGG analysis revealed that oxidative phosphorylation was one of the important pathways. This study gave new perspectives to understand the underlying mechanisms associated with muscle-specific beef quality.